Pengaruh Strategi Pemasaran terhadap Loyalitas Pelanggan dan Volume Penjualan Melalui Kepuasan Pelanggan : (Studi Kasus pada PT. PLN (Persero) UP3 Bulukumba) - Andi Muh. Armin Yusfin; Mahfud Nurnajamuddin; Serlin Serang (Institute Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2025)
This study aims to analyze the impact of marketing strategy on customer satisfaction, customer loyalty, and sales volume, with customer satisfaction acting as a mediating variable. The study employed the Partial Least Squares Structural Equation Modeling (PLS-SEM) method to examine the relationships between variables. Data were collected through surveys using questionnaires distributed to 106 customers selected using the purposive sampling method, targeting customers who had used energy sector services and possessed relevant experience with these services. Data collection was conducted directly, ensuring that respondents met the criteria aligned with the research objectives. The results show that marketing strategy has a positive and significant effect on customer satisfaction, customer loyalty, and sales volume. Additionally, customer satisfaction positively and significantly influences both loyalty and sales volume, and it is proven to mediate the relationship between marketing strategy and customer loyalty, as well as sales volume. These findings affirm that well-designed marketing strategies, such as relevant promotions, competitive pricing, and quality services, play a crucial role in enhancing customer satisfaction, which ultimately strengthens customer loyalty and drives sales growth. This study contributes to the theoretical framework by expanding the literature on marketing in the energy sector, particularly regarding the role of customer satisfaction as a mediator. Practically, the findings recommend that companies focus more on customer-centric marketing strategies to build sustainable long-term relationships. However, the limitations of this study include its restricted geographical scope and its lack of exploration of other variables, such as the role of digital technology. Future research is encouraged to expand the study area and incorporate additional variables for a more comprehensive analysis.